Energy efficiency in the European Union – legal and economic aspects - Gola, Jan; Bobowski, Sebastian (Wydawnictwo Uniwersytetu Wrocławskiego, 2023)
Energy efficiency, understood as measuring energy consumption, is an important element of the energy policy of the state, in particular because of the problem of energy overconsumption by a rapidly growing population and dynamic economic development, particularly with regard to emerging markets and developing countries. Therefore, the issue of energy efficiency requires appropriate legal regulation and a suitable policy pursued by the public authorities. The aim of the article is to describe energy efficiency in the context of the basic assumptions of the economic analysis of law, as well as the importance of the norms of public economic law in the social market economy. The analysis considers the regulatory frameworks of energy efficiency at the level of the European Union and the selected Member State, namely Poland.
Keywords: energy efficiency; European Union; economic analysis of law